2010
DOI: 10.1519/jsc.0b013e3181c7c677
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Practical Assessment Methods to Determine Treadmill, Cycle, and Elliptical Ergometer JOURNAL/jscr/04.03/00124278-201005000-00024/OV0312_8/v/2021-02-09T093711Z/r/image-png O2peak

Abstract: This investigation compared estimated and predicted peak oxygen consumption (VO2peak) and maximal heart rate (HRmax) among the treadmill, cycle ergometer and elliptical ergometer. Seventeen women (mean ± SE: 21.9 ± .3 yrs) exercised to exhaustion on all modalities. ACSM metabolic equations were used to estimate VO2peak. Digital displays on the elliptical ergometer were used to estimate VO2peak. Two individual linear regression methods were used to predict VO2peak: 1) two steady state heart rate (HR) responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…The finding that treadmill testing elicited the highest VO 2 peak is supported by others (11, 17,22). McArdle, Katch and Pechar (23) reported that the treadmill elicits a VO 2 peak 6% to 11% higher than for cycling while we observed a 13% difference between the two modes.…”
Section: Vo 2 In Three Modes Of Exercise 11supporting
confidence: 89%
See 3 more Smart Citations
“…The finding that treadmill testing elicited the highest VO 2 peak is supported by others (11, 17,22). McArdle, Katch and Pechar (23) reported that the treadmill elicits a VO 2 peak 6% to 11% higher than for cycling while we observed a 13% difference between the two modes.…”
Section: Vo 2 In Three Modes Of Exercise 11supporting
confidence: 89%
“…However, the extent that these criteria are achieved in studies is often not reported (2,5,13). Furthermore, the criteria used vary from lab to lab (22). Also, the use of HR peak is common yet many subjects do not achieve this criterion.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…[56][57][58][59][60] Reports also point out that a cycle ergometer test may require an average of 10 additional minutes to achieve maximal effort than tests on treadmills, 61 because (i) subjects on the cycle ergometer have an inability to keep up with their performance; [61][62][63] (ii) a greater activation of MedicalExpress (Sao Paulo, online) 2016 February;3(1):M160102 Cardiopulmonary exercise testing in healthy children Tavares AC large amounts of muscle mass occurs during a treadmill test; 58,59,61 (iii) more discomfort in the thigh muscles occurs during the cycle ergometer test; (iv) less intensity of effort and protocol duration to maximize aerobic energy transfer is achieved on the cycle ergometer. 57,59,61 The 18-20% differences on peak VO 2 values found in this analysis were similar to the 22% difference reported elsewhere; 61 however, smaller differences have also been reported: 7%, 61 8%, 24,64 or 12% higher on a treadmill.…”
Section: Discussionmentioning
confidence: 99%